Effect of Cations in the Background Electrolyte on the Adsorption Kinetics of Copper and Cadmium and the Isoelectric Point of Imogolite - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N (Elsevier B.V., 2015)
Modification of surface charge and changes in the isoelectric point (IEP) of synthetic imogolite were studied for various cations in the background electrolyte (K+, NH4+, Mg2+, and Ca2+). From the electrophoretic mobility data, it was established that the K+ (KCl) concentration does not affect the IEP of imogolite; therefore, KCl is a suitable background electrolyte. In terms of the magnitude of changes in the IEP and surface charge, the cations may be ranked in the following order: Mg2+≈Ca2+NH4+K+. Four different kinetic models were used to evaluate the influence of Mg2+, Ca2+, NH4+, and K+ on the adsorption of Cd and Cu on synthetic imogolite. When adsorption occurs in the presence of cations with the exception of K+, the kinetics of the process is well described by the pseudo-first order model. On the other hand, when adsorption is conducted in the presence of K+, the adsorption kinetics is well described by the pseudo-second order, Elovich, and Weber-Morris models. From the surface charge measurements, the affinity between imogolite and the cations and their effect on the adsorption of trace elements, namely Cu and Cd, were established. © 2015 Elsevier B.V.